2019
DOI: 10.1139/juvs-2018-0035
|View full text |Cite
|
Sign up to set email alerts
|

Successful observation of orangutans in the wild with thermal-equipped drones

Abstract: We investigated the efficacy of a drone equipped with a thermal camera as a potential survey tool to detect wild Bornean orangutans (Pongo pygmaeus) and other tropical primates. Using the thermal camera we successfully detected 41 orangutans and a troop of proboscis monkeys, all of which were confirmed by ground observers. We discuss the potential advantages and limitations of thermal-equipped drones as a tool to complement other methods, and the potential of this technology for use as a future survey tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 16 publications
0
23
0
1
Order By: Relevance
“…Accurate and precise counts of animal populations form the basis of conservation decisions and actions; however, they are lacking for the majority of arboreal species due to difficulties and costs of performing ground surveys. To overcome these difficulties, recent studies have fitted drones with TIR cameras to monitor primate populations (howler monkeys and spider monkeys [23]; orangutans [42]). Here, we demonstrated that a TIR camera fitted to a drone can be successfully employed to determine the presence and count the number of spider monkeys in a closed-canopy forest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accurate and precise counts of animal populations form the basis of conservation decisions and actions; however, they are lacking for the majority of arboreal species due to difficulties and costs of performing ground surveys. To overcome these difficulties, recent studies have fitted drones with TIR cameras to monitor primate populations (howler monkeys and spider monkeys [23]; orangutans [42]). Here, we demonstrated that a TIR camera fitted to a drone can be successfully employed to determine the presence and count the number of spider monkeys in a closed-canopy forest.…”
Section: Discussionmentioning
confidence: 99%
“…The use of drone technology is rapidly changing the way mammal populations are monitored [17], and the addition of a TIR camera has been successful for monitoring small species in open environments (e.g., rabbits [32]) and ungulates in temperate forests [50], but only a few studies have tested its use for surveying arboreal species living in forested environments (e.g., koalas [21]; howler monkeys, spider monkeys, and kinkajous [23]; orangutans [42]). By comparing a substantial dataset obtained by flying the drone while simultaneously counting monkeys from the ground, we were able to demonstrate that the use of a TIR camera is a feasible and valid method of obtaining data on the presence and number of spider monkeys at their sleeping sites in a closed-canopy forest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, aerial survey is an efficient tool for population assessments, as well as for monitoring encroachment, illegal logging, illegal mining, etc. It is important that these surveys are repeated every 5 to 10 years to monitor population trends, and hopefully less expensive techniques, such as drone technology or remote sensing, will improve and can be used in the future [27].…”
Section: Resultsmentioning
confidence: 99%
“…In primates, infrared thermography has been used to assess the behavior of otherwise unobservable nocturnal species (e.g., Rahlfs & Fichtel, 2009;Tan, Yang, & Niu, 2013;Chen et al, 2015). Coupled with drone technology, infrared thermography has been used to provide population estimates by detecting animal heat-signatures in remote, difficult-tonavigate locations (Kays et al, 2018;Spaan et al, 2019;Burke et al, 2019). Facial infrared thermal imaging has been used to quantify the emotional states of non-human primates (Nakayama, Goto, Kuraoka, & Nakamura, 2005;Kuraoka & Nakamura, 2011;Ioannou, Chotard, & Davila-Ross, 2015;Chotard, Ioannou, & Davila-Ross, 2018) and other animals (McCafferty, 2007).…”
Section: Discussionmentioning
confidence: 99%